Desenvolvimento de uma ferramenta multimédia para o Ensino de Desenho Técnico Básico - Nuno Alexandre Macedo de Castro (2016)
This dissertation presents an augmented reality system to aid in the teaching and learning of basic engineering drawing, i.e., the themes, practices and concepts related to the basics of this vast discipline, with a special focus on the reading of objects in represented in pictorial axonometric projection.The document provides a theoretical framework of Engineering Drawing by analysing three major reference works of the portuguese Higher Education system, which in turn forms the foundation of the progression in this discipline. We also provide a framework and a brief historical overview of Multimedia in Education, with a highlight on the affordances of Augmented Reality and Ubiquitous Technologies. The literature survey will also be looking closely at examples of development and implementation of other tools which have been proven successful as a learning aid and as a tool to enhace the spatial thinking and visualization skills of sutdents.This dissertation is, therefore, a companion to the prototype which it describes and should be used a starting point and reference for future studies that can implement and improve it.